2005
DOI: 10.1093/jxb/eri035
|View full text |Cite
|
Sign up to set email alerts
|

Tight regulation of expression of two Arabidopsis cytosolic Hsp90 genes during embryo development

Abstract: The spatial and temporal distribution of expression of two cytosolic members of the AtHsp90 gene family was assessed during early development. In stressed transgenic plants bearing the AtHsp90-3 promoter, beta-glucuronidase (GUS) activity was strong in meristematic tissues. Expression was also detected in vascular tissues, leaf veins, siliques, and in pollen sacs. The promoter induced gene expression after heat shock in a time-course dependent manner. AtHsp90-1 promoter activity was low throughout the early st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 63 publications
(82 reference statements)
7
47
0
Order By: Relevance
“…The mutant phenotypes observed here corroborate recent work showing that AtHsp90-1 is expressed mainly in embryo root tissues, while AtHsp90-3:GUS activity was intense in cotyledons (Haralampidis et al, 2002;Prasinos et al, 2005).…”
Section: Hsp90 and Arabidopsis Development 3515supporting
confidence: 91%
“…The mutant phenotypes observed here corroborate recent work showing that AtHsp90-1 is expressed mainly in embryo root tissues, while AtHsp90-3:GUS activity was intense in cotyledons (Haralampidis et al, 2002;Prasinos et al, 2005).…”
Section: Hsp90 and Arabidopsis Development 3515supporting
confidence: 91%
“…Two CCAAT sequences were identified near the putative HSE. It has been reported that CCAAT-box sequences (representing the binding sites for the C/EBP transcription factors) act cooperatively with HSEs (Rieping and Schoffl 1992;Prasinos et al 2004). Interestingly, no perfect TATA boxes were identified.…”
Section: Athsp90-6 Gene Generates Multiple Transcriptsmentioning
confidence: 99%
“…These proteins are divided into different families, mainly including Hsp60, Hsp70/Hsp80, Hsp90, Hsp110, and a low-molecular weight Hsp (smHsp) family (Al-Whaibi et al, 2011). The Hsp90 gene family contains highly conserved structures and is a molecular chaperone family that exists widely in the eukaryotic cytoplasm (Prasinos et al, 2005). Hsps are involved in protein folding, activation, and maturation, as well as the conformational transition and stability of proteins involved in signal transduction (Prasinos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%